Creation of a collection of different biological sample types from elderly patients to study the relationship of clinical, systemic, tissue and cellular biomarkers of accumulation of senescent cells during aging - A. G. Sorokina; Ya. A. Orlova; O. A. Grigorieva; E. S. Novoseletskaya; N. A. Basalova; N. A. Alexandrushkina; M. A. Vigovsky; K. I. Kirillova; A. V. Balatsky; L. M. Samokhodskaya; N. V. Danilova; U. D. Dyachkova; et al. (Кардиоваскулярная терапия и профилактика)
With aging, tissue homeostasis and their effective recovery after damage is violated. It has been shown that this may be due to the excessive accumulation of senescent (SC) cells in various tissues, which leads to the activation of chronic sterile inflammation, tissue dysfunction and, as a result, to the development of age-related diseases. To assess the contribution of SC cells to human body aging and pathogenesis of such diseases, relevant biomarkers are studied. For successful translation into clinical practice of approaches aimed at regulating the SC cell content in various tissues, it is necessary to study the relationship between the established clinical biomarkers of aging and age-related diseases, systemic aging parameters, and SC biomarkers at the tissue and cellular levels.Aim. To develop and describe action algorithms for creating a biobank of samples obtained from patients aged >65 years in order to study biomarkers of SC cell accumulation.Material and methods. To collect samples, an interaction system was built between several research, clinical and infrastructure departments of a multidisciplinary medical center. At the stage of preanalytical training, regulatory legal acts were developed, including informed consent for patients, as well as protocols for each stage of the study.Results. A roadmap was formed with action algorithms for all participants in the study, as well as with a convenient and accessible system of annotations and storage of biological samples. To date, the collection includes biological samples of 7 different types (peripheral blood serum, formalin-fixed tissue samples and formalin fixed paraffin embedded tissue specimens, samples of different cells isolated from peripheral blood, skin and adipose tissue, samples of deoxyribonucleic and ribonucleic acids, cell secretome conditioned media) obtained from 82 patients. We accumulated relevant anamnestic, clinical and laboratory data, as well as the results of experimental studies to assess the SC cell biomarkers. Using the collection, the relationship between clinical, tissue and cellular biomarkers of SC cell accumulation was studied.Conclusion. The creation of a collection of biological samples at the molecular, cellular, tissue and organism levels from one patient provides great opportunities for research in the field of personalized medicine and the study of age-related disease pathogenesis.